Digital Contract in the Emerging Economy of the 21st Century: A Comparative Study - Jahan, Bushrat (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2024)
In business processes or even our everyday life, the law of contract and proper enforcement of such law play a very significant role. The emerging economy, which is now dependent on the digital world phenomenon, is becoming electronic-based. The era of the internet and social networking is making people decentralized and self-regulated, which attracts online selling and purchasing. So, this is actually the sign of expanding electronic commerce, which makes products more available to the consumers. In this situation, the E-Contract is an aid to drafting and negotiating successful contracts for consumers, businesses, and other related services. It is designed to assist people in formulating and implementing commercial contract policies within e-businesses. As the electronic contract is not a paper-based contract but rather related to cyberspace, there must be specification provisions about such contracts. But in reality, there is a lack of provisions on the formation and regulation of electronic contracts. In developing economies, in countries like Bangladesh, the computerized generation needs more protection, but in many, judgments do not allow computerized documents and even the Information Technology Act, Contract Act, and Evidence Act do not wholly justify electronic contracts. In this paper the legal challenges of electronic contracts will be in focus. The real situation of contract law regarding the electronic contract in the context of Bangladesh compared to other countries will be focused on. The main purpose of this paper is to explore more possible functionalities of e-contracts and ascertain the legal implications.